Dynamics of Cetacean Mixed-Species Groups: A Review and Conceptual Framework for Assessing Their Functional Significance - Syme, Jonathan; Kiszka, Jeremy J.; Parra, Guido J. (Frontiers in Marine Science, 2021)
Numerous species of cetaceans have been recorded in mixed-species groups (MSGs). By forming groups with individuals of different species, cetaceans may reduce predation risk, improve foraging, and gain social benefits. Most accounts of cetacean MSGs, however, are descriptive and little is known about their functions. Furthermore, research has been hindered by inconsistent use of terminology and the lack of a conceptual framework to guide investigations. We reviewed the cetacean literature to compare how MSGs have been termed and defined, to assess their characteristics, to evaluate what is known about their potential functions, and to provide directions for future study. In total, we reviewed 203 studies reporting observations of cetacean MSGs. These MSGs involved 54 different species, predominantly delphinids, that formed 216 different species pairs with varied morphologies and levels of relatedness. Cetacean MSGs occurred across the globe, from tropical to cold temperate seas, from shallow coastal waters to the open ocean, and varied in characteristics such as group size and frequency of occurrence. Only 27 of the reviewed studies proposed and discussed the potential functions of cetacean MSGs, suggesting reduced predation risk (5 species pairs), improved foraging (17 species pairs), and social benefits (12 species pairs) as the main drivers. In most cases, however, the factors that drive the formation of cetacean MSGs remain unknown. Amongst the reviewed studies, MSGs were referred to by various terms, often with no explicit definitions. To reduce this inconsistency, we recommend that future studies use only the term mixed-species group which we define as individuals of two or more species found in close spatial proximity due to mutual or unreciprocated attraction derived from evolutionary grouping benefits. There were also few structured investigations to confirm MSG occurrence and to analyse their potential causes and consequences. To facilitate the study of cetacean MSGs, we developed a conceptual framework that establishes diverse approaches to, firstly, distinguish MSGs from chance encounters and aggregations and to, secondly, investigate their potential functions. This is necessary if we are to advance this field of study and improve our understanding of the role that MSGs play in species and community ecology.